Meta-Analysis of Cytokines and Chemokines in Suicidality: Distinguishing Suicidal Versus Nonsuicidal Patients - Black, Carmen; Miller, Brian J. (Biological psychiatry (1969), 2015)
Major psychiatric disorders are associated with inflammation. Aberrant cytokine and chemokine levels have been associated with psychiatric disorders and suicidal behavior. We performed a meta-analysis of cytokine and chemokine levels in patients with versus without suicidality and patients with suicidality versus healthy controls. We identified articles by searching MEDLINE, PsycINFO, and Thomson Reuters Web of Knowledge databases and the reference lists of identified studies. Study inclusion criteria were met by 18 studies comprising 583 patients with suicidality, 315 patients without suicidality, and 845 healthy control subjects. Levels of interleukin (IL)-1β and IL-6 were significantly increased in blood and postmortem brain samples of patients with suicidality compared with both patients without suicidality and healthy control subjects (p < .05 for each). In vitro IL-2 production by peripheral blood mononuclear cells was significantly decreased in patients with suicidality compared with both patients without suicidality and healthy controls (p < .01 for each). Cerebrospinal fluid levels of IL-8 were significantly decreased in patients with suicidality versus control subjects (p < .05). We found evidence for aberrant cytokine levels in blood, cerebrospinal fluid, and postmortem brain samples of patients with suicidality. Levels of IL-1β and IL-6 were most robustly associated with suicidality, and these cytokines may help distinguish suicidal from nonsuicidal patients. Rigorously designed longitudinal studies are needed to evaluate these associations further.